О предикативной структуре сложных предложений с разночленным и одночленным соподчинением в древнеанглийском языке (На материале Англосаксонской хроники) - Стыро, В. (Kalbotyra, 1975)
Predicative structure of multi-clause sentences consisting of one-member or multi-member coordination clauses is described. Coordination patterns and quantitative distribution of variant patterns are defined.